A Comparative Study of the Prediction of Voltage Collapse in Power System Network - Lilian, Ugonna Ijeoma (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Instability of the power system voltage often results in voltage loss and /or the system collapse, which is a problem for operators and users of power networks. This work presents a stability index suitable for examining the Power System Networks (PSNs) voltage condition. The measure, known as the ABCD Line Stability Index (ABCD_LSI), is derived from a transmission line’s two port network and ABCD parameters using the π-model. It is therefore necessary to treat the equation of the transmission line in the form of complex power and voltage. The goal of the ABCD_LSI index was to predict the voltage collapse of a power system network and also to identify the weakest, associated critical bus lines with respect to a bus for the optimal placement of compensation devices and to investigate the effect of increasing reactive power loading on the PSN. The developed index is then compared to the existing Lmn and Fmn line stability index and was tested on the IEEE 14-bus system using a program coded in the MATLAB environment. The three indices were then simulated for the base case and the contingency- variation of the reactive loads in the network. For the base case, the IEEE 14-bus test system was stable with all the three indices approximately s<1 for all the lines, but it was observed that the new developed index (ABCD_LSI), did not give exact values of the other two indices Lmn and FVSI since the other indices did not consider the length variation of the transmission line in its formulation of their stability index. And this makes the ABCD_LSI more feasible than the other indices even though the other two existing indices could also determine the Voltage stability index of a line.